Challenges Faced by Enterprises in Implementing A Robotic Process Automation (RPA) Solution - Przemyslaw DEMBOWSKI (Communications of International Proceedings, 2022)
More and more entrepreneurs decide to implement Robotic Process Automation technology in their companies, which is associated with facing new challenges that arise at this time. Working with RPA technology is difficult, because on the one hand it is developing very dynamically, providing new functionalities, which means that you have to be up-to-date in order to make the best use of its functionalities. On the other hand, as this technology is still new, there is a lack of appropriate specialists to take full advantage of it. Therefore, modern enterprises must develop an appropriate path of conduct when implementing RPA technology. This can be done first by identifying the problems they will face and breaking them down into prime factors to try to solve them.
Keywords: RPA; Robotic Process Automation; Robotization; BPO Automation